Pengembangan Media Pembelajaran Matematika Interaktif Berbasis Pendekatan Kontekstual: Pengembangan Media Pembelajaran Matematika Interaktif Berbasis Pendekatan Kontekstual - Agung, Agung Setio Nugroho (MEGA: Jurnal Pendidikan Matematika, 2023)
This study aims to produce interactive mathematics learning media based on a contextual approach and determine the quality of interactive mathematics learning media from the aspects of validity, and practicality. The type of research carried out is development research. The development model used is the ADDIE development model which consists of analysis, design, development, implementation, and evaluation. This learning media was created using PowerPoint software, IspringSuite and also Apk Builder Pro. The results showed that the interactive mathematics learning media developed was included in the "very valid" category with a percentage of 98% score. Based on the results of data analysis of student response questionnaires and teacher responses, interactive mathematics learning media is included in the criteria of "very practical" with an average percentage score of 81.4%, while the results of teacher response questionnaires get an average percentage value of 98% with the criteria of "very practical". Based on these results, it can be concluded that learning media is said to be feasible in terms of validity and practicality to be used as student learning media.